Practical guidelines for postmortem examination and tissue sampling of cetaceans for ecotoxicological purposes - Clausen, B. (J. Cetacean Res. Manage., 1999)
Postmortem examinations of marine mammals are undertaken for a number of reasons, inter alia: to determine the possible cause of death; to obtain evidence of diseases or pathological changes; and to collect tissue and other samples (e.g. blood and organs) for further research. The latter can provide material for laboratory studies for a variety of subjects including toxicology, immunology, virology, parasitology and histopathology. The collection of associated biological data such as sex, age, length and nutritional status from each specimen is an essential part of any postmortem examination. Without such data it is very difficult if not impossible to interpret the results of the aforementioned studies.